Chemoselective synthesis of macrocyclic poly(methylvinylsiloxane)s via metathetical ring-expanding polymerization of oligomeric cyclosiloxanes by sequential (MeVinylSi-O-) insertion reactions. Issue 9 (8th February 2017) - Li, Ze; Wu, Chunyong; Liu, Lifeng; Li, Meijiang; Yang, Xiongfa; Hao, Chaowei; Chen, Qiu; Hu, Ziqiang; Luo, Mengxian; Lai, Guoqiao; Luh, Tien-Yau
Abstract : Macrocyclic poly(methylvinylsiloxane)s were synthesized chemoselectively. Abstract : Macrocyclic polysiloxanes are useful materials for the development of interpenetrating polymer networks and thermally stable materials. The main drawbacks of reported methods for the preparation of macrocyclic polysiloxanes are that mixtures of linear and cyclic polysiloxanes are commonly obtained, and complex and time-consuming separation processes are needed. Moreover, the preparation of macrocyclic polysiloxanes occasionally needs harsh conditions, and in general has low efficiency. In this research, we find that highly pure macrocyclic poly(methylvinylsiloxane)s (cPMVSs) can be chemoselectively prepared from 1, 3, 5, 7-tetramethyl-1, 3, 5, 7-tetravinylcyclotetrasiloxane with water catalyzed by anhydrous iron(iii ) chloride in high efficiency. The structure of cPMVSs is characterized by gel permeation chromatography, infrared spectroscopy, 1 H- and 29 Si-nuclear magnetic resonance (NMR), and viscosity. Thermogravimetric analysis shows that cPMVSs have excellent thermal stability. A metathetical ring-expanding polymerization mechanism is proposed.